Extended Advance Of Continuous Miner Successfully Ventilated With A Scrubber In A Blowing Section (Society for Mining, Metallurgy & Exploration, 1986)
Underground testing was carried out by Ingersoll-Rand, Inc., under contract to the Bureau of Mines to determine the effectiveness of a machine-mounted scrubber system for ventilating the face during an extended advance. A continuous miner equipped with an integral flooded-bed dust scrubber system was instrumented with methanometers and Real-time Aerosol Monitor (RAM) dust monitors. Methane and respirable dust data were collected at brattice setbacks of 7.5 m (current operating distance), 10.5 m, and 15 m (blowing ventilation) during production shifts. Results showed that a suitable machine-mounted scrubber system can adequately ventilate the face at brattice setbacks up to 15 m. No deterioration in ventilation performance was observed as brattice setbacks were increased from 7.5 m to 15 m. The scrubber system effectively controlled face methane levels at large setbacks, though respirable dust levels increased as much as 33 pct at the operator's cab at setbacks greater than 7.5 m.